The Perception of Health Belief and Vaccine Valence Towards Domestic Tourist Intention to Travel during COVID-19 Pandemic - Rozilawati Shaari; Wan Rusni Wan Ismail; Nor Hafizah Mazlan; Wan Ilinajwa Wan Mustaffa; Norliana Hashim (Information Management and Business Review, 2024)
This research investigates health risk perception and vaccine valence as factors that affect Malaysian intention to engage in domestic vacations. An online survey was created with Google Forms and distributed to a sample of 265 domestic travellers at least 18 years of age in May and June 2021; this is when the nationwide vaccine program started in Malaysia. The result indicates that vaccine valence risk perception was a significant factor in affecting domestic vacation intention. Only perceived behavioural control and subjective norms mediated the relationship between health risk perception and domestic vacation intention.  Overall, vaccine valence risk perception tested significantly with all constructs in this study due to the various factors, especially the timing of data collection where the data collection was carried out amid the national vaccination program. Hence, the vaccine is now perceived as a hope for many as the solution to the current pandemic problem. It indicates that domestic vacationers will return once vaccinated and when tourism sectors are open for business and resume their regular operation. These findings extend the body of knowledge for the theory of health belief and theory of planned behaviour in predicting tourist intention to travel during a pandemic. Findings also indicate the positive impact of vaccine valence on the tourist's intention to travel, which provides a glimpse of future tourist behaviour when facing similar uncertainties.